2003
DOI: 10.1046/j.1439-0531.2003.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte and Embryo Quality: Effect of Origin, Culture Conditions and Gene Expression Patterns

Abstract: In general, the majority of immature bovine oocytes fail to develop to the blastocyst stage following maturation, fertilization and culture in vitro. The evidence suggests that while culture conditions during in vitro embryo production can impact on the developmental potential of the early embryo, the intrinsic quality of the oocyte is the key factor determining the proportion of oocytes developing to the blastocyst stage. In addition, evidence suggests that the period of post-fertilization embryo culture is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
1
22

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(198 citation statements)
references
References 115 publications
(211 reference statements)
5
170
1
22
Order By: Relevance
“…The ability of in vitro produced embryos to survive cryopreservation, an indicator of embryo quality [4,5,8,12,41,42], is affected by culture conditions. Thus, Dinnyés et al [29] reported high survival rates (85% and 90%) after vitrification/warming of Day 8 expanded embryos produced in SOF without and with FCS, respectively; the hatching rates the above authors obtained for embryos produced in SOF + FCS (63%) are comparable to the survival rates in our work in the Vero and BSA groups.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of in vitro produced embryos to survive cryopreservation, an indicator of embryo quality [4,5,8,12,41,42], is affected by culture conditions. Thus, Dinnyés et al [29] reported high survival rates (85% and 90%) after vitrification/warming of Day 8 expanded embryos produced in SOF without and with FCS, respectively; the hatching rates the above authors obtained for embryos produced in SOF + FCS (63%) are comparable to the survival rates in our work in the Vero and BSA groups.…”
Section: Discussionmentioning
confidence: 99%
“…These events start with the ability of the oocyte to complete maturation and then to undergo successful fertilization, cleavage and reach the blastocyst stage producing a good-quality embryo (Sirard et al, 2006). Although succeeding in one of these events does not guarantee success in the next, oocyte maturation is considered a critical step that influences the success of fertilization and subsequent embryo development (Lonergan et al, 2003). While $60% of in-vivo matured bovine oocytes reach the blastocyst stage when fertilized and cultured in vitro, less than 40% of oocytes matured in vitro do so.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to achieve such development, known as oocyte competence, is acquired mainly during the antral phase of folliculogenesis through wellcoordinated molecular processes, including proper nuclear maturation and final cytoplasmic maturation (Sirard et al 2003, Krisher 2004, Kimura et al 2007. Successful oocyte final maturation is therefore a complex process that implies many factors such as intrinsic oocyte quality (Lonergan et al 2003, Wang & Sun 2007, dialog with neighboring somatic compartment (Matzuk et al 2002, Tanghe et al 2002, Yokoo & Sato 2004, Gilchrist et al 2008, Li et al 2008, and functional gap junctions (Thomas et al 2004, Lodde et al 2007. It has been established that, inside the follicle, the oocyte is surrounded by granulosa cell (GC) populations that, through folliculogenesis, differentiate into both mural GCs and cumulus cells (CCs).…”
Section: Introductionmentioning
confidence: 99%